Islamic Views on the Role of Philosophy in the Formation of Science and Ethics According to Al-Ghazali's Thought - Arrazet, Harun; Syarifuddin, Syarifuddin; Abrianto, Danny (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background:Philosophy, science, and ethics are three essential pillars of the Islamic intellectual tradition. However, in modern practice, a disconnect between science and ethics often occurs, giving rise to various moral deviations. Al-Ghazali's thought offers an integrative framework that combines rationality, spirituality, and morality as the foundation for developing knowledgeable and moral individuals. Aims:This study aims to analyze the role of philosophy in the formation of science and ethics according to an Islamic perspective based on Al-Ghazali's thoughts, and to explain how the integration of the two can be a solution to contemporary ethical problems. Methods:The study employed a qualitative design with a library research approach. Data were obtained through analysis of Al-Ghazali's works and relevant classical and contemporary literature, then analyzed using content analysis methods. Result:The research results show that philosophy plays a crucial role in guiding reason to understand the truth through a proper scientific process, while simultaneously strengthening ethics as a moral foundation. Al-Ghazali accepted aspects of philosophy that were in harmony with Islam, particularly logic, epistemology, and morality, while rejecting those that contradicted his creed. The integration of philosophy, science, and ethics is reflected in his works such as Ihya' Ulumuddin and Al-Munqidz min al-Dhalal. Conclusion:Al-Ghazali's thinking asserts that knowledge without ethics is empty, while ethics without knowledge is unsound. Philosophy serves as a bridge to harmonize the two through the integration of reason and revelation, thus serving as a foundation for educational development and character formation in the modern era.